KEPEMIMPINAN TRANSFORMASIONAL DALAM BUDAYA ORGANISASI - Masine Slahanti; Ani Setyowati (Universitas Muhammadiyah Surakarta, 2021)
The role of the leader in an organization is the key factor to determin the success of the organization. By the organization leader, the members will be more easily managed and controled. Transformational leadership is one of leadership style that is able to create intrinsic motivation for organizational members. This study to determine the meaning of transformational leaders to create a better work culture in the company. This study uses a phenomenological method that focused on PT. Serkolinas Aman Nusantara Semarang. To obtain research results, researchers used unstructured interviews in extracting information. Unstructured interviews were addressed to nine number of employees at PT. Serkolinas Aman Nusantara Semarang. Research shows that the transformational type of leader style is able to create a positive work culture in the organization. Because, transformational leadership style is able to direct the behavior of organizational members to create value in accordance with organizational goals, thus ignoring the personal vision of organizational members.